Motivation Forms Regarding the Pro-Social Behaviour of the Teenagers at School. - TALLUSHI, Esjurda; BIBA, Gjylse; ISUFI, Temisa (European Journal of Sustainable Development, 2016)
Teenagers are considered a vulnerable group, not only due to the characteristics of their age, but also due to the high risk of their involvement in asocial behavior, as a result of many social problems, duality of values, confusion regarding decision-making at an early age, the absence of positive models to follow, not only at school, in the community, but also within their family. In the Albanian reality particularly, the building of self-esteem is not the only influencing element, in the formation of the concept on oneself, and the concept of personality, but also the frustration of a society, that has gone through a long period of transition, the aftermath of a dictatorship. On these grounds, the motivation forms of positive behavior have been influenced by the family authority, rule obedience as an escape from punishment, and not as a result of awareness, reward, and proper methods of teaching in schools. The aim of this work is to explore the motivation forms of the pro-social behavior, for the purpose of avoiding asocial behavior of teenagers in schools, via the effective communication, positive models, constructive teaching methods, proper parenting styles, socializing processes, removal of attention from asocial behavior and the providing of proper models to follow. The method used in this work will be the mixed research (qualitative and quantitative). Part of this study will be teenagers aged 15-17 years old (boys and girls) of a high school in the city of Kavaja (Albania) through filling out half structured questionnaires . We have interviewed also professional teachers, parents, social workers and psychologists, in order to provide a clear panorama of this context, by analyzing with existing cases and well determined intervention that bring forth a strengthening of positive behaviors and avoidance of asocial behaviors in teenagers. The findings of this study are closely related with the importance of any form of motivation in schools, in the teacher-teenager relationship, cooperation between their peers, the parent-teenager relationship in the implementation of the resulting positive attitude, through teaching a system of values and anti-values, the psycho-social motivating intervention during the teaching process that will be widely analyzed and that open many paths for further studies. Key words: teenager, pro-social behavior, motivation, teacher, psycho-educational intervention, communication, parent, socialization.